Implementation of Song Media in Improving Arabic Listening Skills of Elementary School Students - Gilbran Akbar; Abdul Hakim Febridalsyah; K.A. Rahman; Warissuddin Soleh (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to explain how interactive learning strategies using songs can improve students' listening skills in Arabic lessons in fifth-grade students at an Islamic elementary school in Jambi City. This research is based on students' low listening skills, which are caused by the use of traditional teaching methods and the lack of use of engaging audio media. The study shows that implementing interactive learning strategies using songs can significantly improve students' listening skills.